Polarization switching in PVDF ferroelectric polymer composites containing graphene layers: molecular dynamic simulations - Bystrov, Vladimir (2021)
In this work molecular modeling and quantum molecular dynamic (MD) calculations studies composite nanostructure containing ferroelectric polymer PVDF and graphene layers were carried out using HyperChem software and PM3 semi-empirical method. It is shown that the inclusion (addition) of graphene layers to the ferroelectric PVDF polymer increases the coercive field of the composite structure and decreases the polarization switching times of this composite heterostructure. The data obtained predict possible new compositions of such nano and heterostructures with altered or adjustable times of polarization switching and coercive fields, which can be promising for applications.